THE EFFECTS OF NITROGLYCERIN ON THE PROLIFERATIVE AND MIGRATORY POTENTIAL OF PERIPHERAL BLOOD MONONUCLEAR CELLS - N. A. Bondarenko; A. P. Lykov; I. I. Kim; O. V. Poveschenko; A. F. Poveschenko; E. A. Pokushalov; A. B. Romanov; V. I. Konenkov; A. M. Karaskov (Вестник трансплантологии и искусственных органов, 2014)
Aim. To study the effects of nitroglycerin on proliferative and migratory activity of mononuclear cells and endothelial progenitor cells in patients with chronic heart failure.Materials and methods. Proliferative potential of peripheral blood mononuclear cells in donors and patients were studied in MTT-test in the presence of 50 and 100 mg/ml nitroglycerin. Proliferation and migration of endothelial progenitor cells in patients were evaluated by changes in the cell impedance in real-time in the presence of various doses of nitroglycerin.Results. It is shown that nitroglycerin reduces in vitro both spontaneous and Concanavalin A stimulated proliferative activity of mononuclear cells in patients with chronic heart failure. Peripheral blood mononuclear cells in patients with chronic heart failure, obtained after procedure of mobilization by granulocyte colony-stimulating factor respond to nitroglycerin dose of 50 mg/ml with the increased proliferative activity, and with the suppressed proliferative activity to nitroglycerin dose of 100 mg/ml. Mononuclear cells of healthy donors respond to 50 mg/ml of nitroglycerin with the activation of proliferative capacity, but at a dose of 100 mg/ml spontaneous proliferative activity of mononuclear cells inhibit. It is also shown that the presence of nitroglycerin in medium dose in stimulating test leads to the inhibition of mononuclear cells proliferation from healthy donors. It is shown the stimulating effect of nitroglycerin on proliferative and migration potential of endothelial progenitor cells.Conclusion. Multidirectional and dose-dependent effects of nitroglycerin to the various types of human cells in vitro were observed.